2021
DOI: 10.3390/ijms22189707
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Phenolic Metabolites and Skin Cancer

Abstract: Skin cancer represents any tumor development from the cutaneous structures within the epidermis, dermis or subcutaneous tissue, and is considered to be the most prevalent type of cancer. Compared to other types of cancer, skin cancer is proven to have a positive growth rate of prevalence and mortality. There are available various treatments, including chemotherapy, immunotherapy, radiotherapy and targeted therapy, but because of the multidrug resistance development, a low success has been registered. By this, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 155 publications
0
10
0
Order By: Relevance
“…In addition, the use of natural compounds might reduce the side effects of standard therapy. Previous studies have shown that polyphenols demonstrate anticancer properties on melanoma cell lines via their cytotoxic and anti-proliferative effects and also by participating in the regulation of cell cycle, apoptosis and autophagy [ 22 ]. Martino et al [ 23 ] suggested that the extract from Larrea divaricata Cav.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of natural compounds might reduce the side effects of standard therapy. Previous studies have shown that polyphenols demonstrate anticancer properties on melanoma cell lines via their cytotoxic and anti-proliferative effects and also by participating in the regulation of cell cycle, apoptosis and autophagy [ 22 ]. Martino et al [ 23 ] suggested that the extract from Larrea divaricata Cav.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols have already been used in dermatology and are known to exert antiproliferative, proapoptotic, and antimetastatic activities on melanoma cell lines, whereas they have no cytotoxic effect in healthy cells [ 53 , 54 ]. Since ferroptotic pathways contribute to the regulation of the differentiation state of melanoma cells and their resistance to certain therapeutic agents, ferroptosis inducers are expected to have strong therapeutic potential in melanoma [ 55 ].…”
Section: Biological Aspects Of Ferroptosis Modulatorsmentioning
confidence: 99%
“…In terms of health properties, many studies have demonstrated their various biological activities including anti-inflammatory, anticancer, antibacterial and antiviral properties. Specific flavonoids were described to function as antioxidants, enzyme inhibitors, epigenetic modulators or even suppressors in some signaling pathways [72,73].…”
Section: Flavonoids and Human Healthmentioning
confidence: 99%